First Record of Mermithidae (Enoplea: Mermithida) Parasitizing Philaenus spumarius (Hemiptera: Aphrophoridae) in Central Italy - Nencioni Anita; Bigiotti Gaia; Gargani Elisabetta; Sacchetti Patrizia; Strangi Agostino; Cutino Ilaria (Journal of Nematology)
Philaenus spumarius specimens were found naturally parasitized by Mermithidae nematodes in Central Italy. Nematodes infected all spittlebug instars, showing a highly variable parasitization rate according to sampling locations. Molecular analysis highlighted the presence of two distinct species that are apparently not cohabitant in the same site. However, complete taxonomic identification will occur when adult nematodes are obtained. Further research is needed to identify these two putative nematode species and to understand their ecological requirements. Furthermore, new studies aimed to elucidate the relationship between P. spumarius and Mermithidae nematodes, as well as the role of these parasites in regulating spittlebug populations, can be useful in identifying potential natural enemies for pest control. To our knowledge, this is the first report of Mermithidae infecting P. spumarius in Europe.